Crop prediction based on geographical and climatic data using machine learning and deep learning - Alif, Al Amin; Shukanya, Israt Farhana; Afee, Tasnia Nobi (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.